Performance analysis of an STFT-based broadband interference excision algorithm in DS-SS systems - Aldirmaz, Sultan; Durak, Luetfiye (IEEE, 2007)
A novel short-time Fourier transform (STFT)based interference excision algorithm in direct-sequence spread spectrum (DS-SS) communication systems is introduced. The proposed excision algorithm is developed for chirp-type signals that have broadband frequency characteristics. It is based on the time-frequency analysis of received signals. To analyze the interference, STFT of the received signal is computed and thresholded. The interference detection is followed by an inverse-STFT computation to estimate the high power jamming signal. The estimated jammer is then subtracted in time domain before demodulation. Simulations present adequate interference estimation results with mean estimation errors less than 0.01%. Various scenarios with different jammer-to-signal ratios (JSRs) and signal-to-noise ratios (SNRs) vs. bit error rates (BERs) are presented for single and multi-component chirp signals. Interference excision algorithms improve the system performance more than an order of magnitude.
Keywords: Computer Science; Engineering; Telecommunications